Peningkatan Kemampuan Anak dalam Mengenal Konsep Bilangan Melalui Penggunaan Media Pembelajaran Berbasis Alam - Abdul Syukur; Yulianty Thabita Fallo (PG-PAUD Trunojoyo, 2019)
Enhancing Early Childhood Ability to Know the Concept of Numbers through Using of Learning Media Based on Nature. The purpose of this study is to improve the ability of children to understand the concept of numbers through using of learning media based on nature.  The type of research conducted is Classroom Action Research with data collection techniques in the form of observations and performance and then analyzed using qualitative descriptive analysis techniques. This research was conducted in two cycles, namely cycle I and cycle II. In the first cycle the percentage of student performance achieved 30% of the percentage before use the cycle, in this cycle students who managed to achieve the Minimum Completeness Criteria drove 11 people who had not succeeded in achieving a large of minimum completeness criteria students could participate in learning activities well and encourage very active when using media. So the research continued the second cycle in cycle II, the percentage reached 45% and all students who succeeded in reaching 20 people managed to reach the minimum completeness criteria while the observations showed that students were very interested in learning to use the prepared media. From the results of the implementation of the first cycle and the second cycle the increase in the percentage of student learning completeness reached 75% of the percentage before cycle use. Thus, it can be denied that the learning media based on nature can improve the ability of children to understand the concept of numbers to support learning activities in early childhood can use media that are either natural media or media that have been supportive in order to produce learning that is conducive to children's abilities.